Negotiating currency internationalization: An infrastructural analysis of the digital RMB - Harry Deng (Finance and Society, 2024)
In what ways might the digital renminbi (RMB), also known as e-CNY, bolster China’s efforts to internationalize its currency? Utilizing Susan Strange’s concept of currency negotiation and borrowing the concept of infrastructures from science, technology, and society studies, this article argues that RMB internationalization is a gradual process that relies heavily on negotiation involving both state and non-state actors (i.e., private financial authorities). It further argues that while e-CNY may create new opportunities for RMB internationalization, it also raises new challenges. First, the e-CNY’s lack of coordination with other central banks represents a challenge for future evolution and standardization with other digital currency platforms, thus rendering first-mover status a potential disadvantage. Second, as a result of China’s divergent data governance direction from both the US and the EU, the e-CNY is disadvantaged when it comes to interoperability, trust of users, and diversity of data. The purpose of this study is not to predict the future of RMB internationalization once the e-CNY rolls out but rather to highlight various ways in which the latter may influence the former in order to widen analyses of the topic.